Selective Stimulability in the Speech and Language Assessment of Bilingual Children with Selective Mutism - Elizabeth Harbaugh , M.S., CCC-SLP; Raul F. Prezas , Ph.D., CCC-SLP; Robin L. Edge , Ph.D., CCC-SLP (Journal of Human Services: Training, Research, and Practice, 2018)
English Language Learners (ELLs) with Selective Mutism (SM) mirror their typically developing, bilingual peers who are going through the silent period. The silent period is a normal phenomenon characterized by decreased expressive language and a general lack of communication that is temporary. Understanding second language acquisition and differentiating SM from the silent period, however, is critical to reduce over- and under-identification of children for services. Whereas bilingual children with SM do not speak in either of their languages, bilingual children in the silent period are only silent in their second language. Although limited information exists regarding assessment and treatment for SM in ELLs, general assessment and intervention strategies are available. The notion of selective stimulability (how stimulable a child with SM is for expressive communication) may be used in assessment in order to encourage children with SM to communicate expressively when using speech and language protocols and for determining prognosis for treatment. Guidelines for differential diagnosis of SM and the silent period are offered in this paper, including a case example of the use of selective stimulability in a speech-language assessment of a Spanish-speaking child. Moreover, additional information related to the assessment process and implications for intervention are provided.